Feasibility of Pre-Harvest Sago Frond as State-of-the-Art Resources to Produce Animal Feed - Muhammad Norhelmi, Ahmad; Kopli, Bujang; Dayang Salwani, Awang Adeni; Nurashikin, Suhaili; Andrian Susin, Ambud (Penerbit Universiti Sultan Zainal Abidin, Malaysia (UNISZA), 2024)
Global crises such as climate change, war and borderless diseases are the factors that lead to limited supply and unstable prices of the raw material to produce animal feed placing a major burden on the farmers and smallholders to produce livestock at a reliable cost. Malaysia is among the most affected country due to its high dependency on imported resources to produce animal feed. Hence, cheap and locally available raw material is the key to producing sustainable and safety-ensured animal feed for domestic consumption. Due to the adaptability and resilient nature of sago palm towards extreme environmental distress, sago frond was selected as an alternative raw material to produce animal feed in the form of silage. Sago frond was pruned from growing sago palm (age between 3-7 years), then leaves and rachis were pulverised before vacuum packed into silo bag. Analysis shows that optimised sago frond silage (1:1 RSF/SL) possessed five ideal characteristics that include dry matter (47.76 %), acid detergent fibre (31.98 %), total water-soluble sugar (2.4 g/Kg), minimum pH (4.3) and protein content (16.85 %). Hence, the ensiling technique applies to produce high-quality animal feed from optimum formulated sago frond by preserving nutrient content and improving in-vitro digestibility of the silage designated for ruminant consumption. The feeding trial shows significant growth performance of animal models (Malin Breed Sheep) fed with optimised SFSil with Average Daily Gain (61.12 g/day) and Feed Conversion Ratio (9.64 g/g). Therefore, manufacturing animal feed from pre-harvest sago frond provides the solution to high dependency on imported animal feed and also offers a new lucrative commodity for the sago farmers while waiting for the sago palm to be harvestable.